Synthesis of aromatic poly(amide-imide)s from novel diimide-diacid (DIDA) containing sulphone and bulky pendant groups by direct polycondensation with various diamines - Patil, Prashant S.; Pal, Ravindra R.; Salunkhe, Manikrao M.; Maldar, Noormahamad N.; Wadgaonkar, Prakash P. (European Polymer Journal, 2007)
A novel diimide-diacid (DIDA) monomer, 4-{4-[(4-methyl phenyl) sulphonyl]}-1,3-bis-trimellitoimido benzene containing sulphone and bulky pendant groups was successfully synthesized and used to synthesize a series of wholly aromatic poly(amide-imide)s (PAIs) by direct polycondensation method. The direct polycondensation of newly synthesized DIDA with different diamines was carried Out via Yamazaki's phosphorylation method using triphenyl phosphite and pyridine system. The resulting poly(amide-imide)s were obtained in quantitative yields with inherent viscosities 0.36-0.47 dl/g in DMAc at 30 +/- 0.1 degrees C. The poly(amide-imide)s were amorphous and were readily soluble in various solvents such as N-methyl-2-pyrrolidinone (NMP), NN-dimethylacetamide (DMAc), N,N-dimethylformamide (DMF), dimethylsulfoxide (DMSO), and pyridine. Tough and flexible films were obtained by casting their DMAc solution. According to thermogravimetric analysis, the polymers were fairly stable up to temperature around 396 degrees C, and 10% weight losses in the temperature range of 476-511 degrees C that showed good thermal stabilities of these polymers. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: direct polycondensation; poly(amide-imide)s; sulphone and bulky pendant groups; thermally stable polymers

Synthesis, characterization and constitutional isomerism study of new aromatic polyamides containing pendant groups based on asymmetrically substituted meta-phenylene diamines - Pal, Ravindra R.; Patil, Prashant S.; Salunkhe, Manikrao M.; Maldar, Noormahamad N.; Wadgaonkar, Prakash P. (European Polymer Journal, 2009)
Four new aromatic polyamides containing pendant groups were synthesized by low temperature interfacial polycondensation of two asymmetrically substituted diamine monomers, namely, 4-[4-(1-methyl-1-phenylethyl) phenoxyl-1,3-diamino benzene and 4-[4-[4-methylphenyl) sulphonyl]phenoxy)-1,3-diamino benzene with two aromatic diacid chlorides, namely isophthaloyl chloride and tereplithaloyl chloride. Inherent viscosities of polyamides were in the range 0.64-0.72 dL/g indicating formation of medium molecular weight polymers. The weight average molecular weights and number average molecular weights, determined by gel permeation chromatography (polystyrene standard), were in the range 54,500-65,000 and 19,750-27,000, respectively. The constitutional isomerism of synthesized polyamides was investigated by (1)H and (13)C NMR spectroscopy, where as the constitutional order was calculated from (1)H NMR spectroscopy and was found to be in the range 0.35-0.37. Polyamides containing pendant groups were essentially amorphous and were soluble in polar aprotic solvents such as N, N-dimethyl acetamide, N-methyl-2-pyrrolidone, N, N-dimethyl formamide and dimethyl sulfoxide. Polyamides exhibited glass-transition temperature in the range 237-254 degrees C. The initial decomposition temperature, determined by TGA in nitrogen atmosphere, of polyamides was in the range 371-410 degrees C indicating their good thermal stability. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Asymmetrically substituted diamines; Constitutional isomerism; interfacial polycondensation; Pendant groups

Synthesis, spectroscopy, and electrochemical investigation of new conjugated polymers containing thiophene and 1,3,4-thiadiazole in the main chain - Patil, Prashant S.; Haram, Nanda S.; Pal, Ravindra R.; Periasamy, N.; Wadgaonkar, Prakash P.; Salunkhe, Manikrao M. (Journal of Applied Polymer Science, 2012)
Novel photoluminescent donoracceptor poly(p-phenylenevinylene)-type conjugated polymers containing thiophene and 1,3,4-thiadiazole units in the main chain were synthesized from 2,5-bis(5-bromomethyl-2-thienyl)-1,3,4-thiadiazole and 1,3/1,4-benzenedialdehyde by WittigHorner reaction. The synthesized polymers were characterized by the use of thermal analysis and spectroscopic (infrared, UV-visible absorption, and photoluminescence) measurement. The resultant material exhibited bluish green, green, and orange fluorescence in their solution and thin film and solid forms, respectively. The redox property of the polymers has also been studied by cyclic voltammetry. The optical and electrochemical studies reveal that these novel polymers are new promising materials for the development of efficient polymer light-emitting diodes. (c) 2012 Wiley Periodicals, Inc. J Appl Polym Sci, 2012
Keywords: conjugated polymers; photoluminescence; thiophene and thiadiazole-containing polymer